Implikasi Naskh Dalam Penafsiran Al-Qur'an - Muslimah, Neng Rahmila (Al-Fath, 2021)
The concept of naskh still an interesting issue in the study of the Qur’an both in the classical and contemporary era. This can be seen from various interpretations in addressing the verses that are considered contradictory. This is the task of academics in the field of the Qur’an to uncover the concept of naskh, especially the initiators of the naskh theory in the contemporary era which have different criticisms and opinions regarding the concept of naskh it self. Thus, the question will arise, are there any verses in the Qur’an which are contradictory? are there any verses that are dysfunctional? this problem has caused controversy among the ulama.